Social media discussion of sell-side analyst research: evidence from Twitter - Call, Andrew C.; Kara, Mehmet C.; Peterson, Matt; Weisbrod, Eric (Review of Accounting Studies, 2026)
Abstract We examine Twitter discussion of sell-side analysts’ stock recommendation revisions. While many investors lack direct access to analyst research, we observe revision-related Twitter discussion associated with approximately 90 percent of the revisions in our sample, usually within three hours of their announcement. Revision-related Twitter discussion is greater for upgrades and for analysts from larger brokerages. Examining within-revision intraday price discovery, we observe increased price discovery during intraday windows with more revision-related tweets, especially for tweets that have more user engagement, are posted by more influential authors, or involve stocks with more intense retail trading volume. We find that revision-related retail trading is more intense and better predicts future returns for revisions with more revision-related Twitter discussion. We observe no such evidence for institutional investors who have direct access to sell-side research. Our results suggest that Twitter is an important channel in facilitating price discovery following analyst revisions, particularly among retail investors.